Efektivitas Ekstrak Daun Mangifera indica L. Menghambat Candida albicans pada Plat Resin Akrilik Heat-cured - IGA Kade I. Purbasari; Desak N. A. Susanti; Ni Ketut A. Lestarini (Universitas Sam Ratulangi, 2023)
Abstract: Heat-cured acrylic resin dentures are used to treat tooth loss, however, pores are easily formed on their surfaces which make it easier for Candida to adhere. Improper maintenance of dentures can cause overgrowth of Candida albicans and trigger denture stomatitis. This study aimed to determine the effectiveness of Mangifera indica L. extract on inhibition of Candida albicans on heat-cured acrylic resin plates. This was a true experimental laboratory study with a post-test only control group design. Samples were heat-cured acrylic resin plates contaminated with Candida albicans. The treatment groups were chlorhexidine gluconate 0.2%, aquades, and extract with concentrations of 65%, 75%, 85%, and 100%. Samples were immersed in the treatment groups for 15 minutes, followed by dilution and culture on SDA media, and then fungal colonies were observed. Data were analyzed with the Shapiro-Wilk normality test, the Levene's test for homogeneity, continued with the parametric one-way ANOVA and post hoc least significant difference tests. The results showed significant differences between the treatment groups (p<0.05). The percentage of the extract group with the lowest number of fungi was 75%, meanwhile the highest one was 65%. In conclusion, Mangifera indica L. leaf extract is effective in inhibiting the growth of Candida albicans on heat-cured acrylic resin plates with an optimal concentration of 75%. Keywords: mango leaf extract (Mangifera indica L.); Candida albicans; heat-cured acrylic resin Abstrak: Gigi tiruan resin akrilik heat-cured digunakan untuk mengatasi kehilangan gigi, namun sering terbentuk porus pada permukaannya yang mempermudah perlekatan Candida. Pemeliharaan gigi tiruan yang tidak tepat dapat menyebabkan pertumbuhan Candida albicans berlebihan dan memicu terjadinya denture stomatitis. Penelitian ini bertujuan untuk mengetahui efektivitas ekstrak daun mangga arum manis (Mangifera indica L.) dalam menghambat Candida albicans pada plat resin akrilik heat-cured. Jenis penelitian ialah true experimental laboratory dengan post test only control group design menggunakan sampel plat resin akrilik heat-cured yang dikontaminasi Candida albicans. Kelompok perlakuan yaitu chlorhexidine gluconate 0,2%, akuades, ekstrak konsentrasi 65%, 75%, 85%, dan 100%. Sampel direndam pada kelompok perlakuan selama 15 menit, dilanjutkan dengan tahap dilusi serta kultur pada media SDA, diakhiri dengan pengamatan koloni jamur. Analisis data menggunakan uji normalitas Shapiro Wilk, uji homogenitas Levene, dan dilanjutkan dengan uji parametrik One-Way ANOVA, dan Post Hoc Least Significant Difference. Hasil penelitian mendapat-kan perbedaan bermakna antar kelompok perlakuan (p<0,05). Kelompok ekstrak dengan angka jamur terendah ialah konsentrasi 75% dan yang tertinggi ialah konsentrasi 65%. Simpulan penelitian ini ialah ekstrak daun mangga arum manis (Mangifera indica L.) efektif dalam menghambat pertumbuhan Candida albicans pada plat resin akrilik heat-cured dengan konsentrasi optimal 75%. Kata kunci: ekstrak daun Mangifera indica L.; Candida albicans; resin akrilik heat-cured